Radar techniques using array antennas - Wirth, Wulf-Dieter (London, United Kingdom The Institution of Engineering and Technology, 2013)
The book covers the following areas: radar technique; array antenna; signal representation; mathematical tools; statistical signal theory; adaptive beamforming; signal sampling; signal digitisation; pulse compression; polyphase code; target detection; sequential detection; jammer suppression; monopulse direction estimation; array processing; space-time adaptive processing; inverse synthetic aperture radar; active phased array; target classification; floodlight; MIMO radar; and passive radar.
Electronic reproduction.
Keywords: Radar; Antenna arrays; Electronic books